Polymers with distinctive anticancer mechanism that kills MDR cancer cells and inhibits tumor metastasis. (April 2019) - Zhong, Guansheng; Yang, Chuan; Liu, Shaoqiong; Zheng, Yiran; Lou, Weiyang; Teo, Jye Yng; Bao, Chang; Cheng, Wei; Tan, Jeremy P.K.; Gao, Shujun; Park, Nathaniel; Venkataraman, Shrinivas; et al.
Abstract: Although mortality continues to decline over the past two decades, cancer is still a pervasive healthcare problem worldwide due to the increase in the number of cases, multidrug resistance (MDR) and metastasis. As a consequence of multidrug resistance, cancer treatment must rely on a host of chemotherapeutic agents and chemosensitizers to achieve remission. To overcome these problems, a series of biodegradable triblock copolymers of PEG, guanidinium-functionalized polycarbonate and polylactide (PEG-PGCx -PDLAy ) is designed as chemotherapeutic agents. These copolymers self-assemble into micellar nanoparticles, and are highly effective against various cancer cell lines including human breast cancer (BCap37), liver cancer (HepG2), lung cancer (A549) and epidermoid carcinoma (A431) cell lines as well as MDR Bats-72 and Bads-200 cancer cells that were developed from BCap37. Multiple treatments with the polymers at sub-lethal doses do not induce resistance. The polymers kill cancer cells by a non-apoptotic mechanism with significant vacuolization and subsequent membrane disruption. In vivo antitumor efficacy is evaluated in a metastatic 4T1 subcutaneous tumor model. Treatment with stereocomplexes ofPEG-PGC 43 -PLLA 19 andPEG-PGC 43 -PDLA 20 at a dose of 20 mg/kg of mouse body weight suppresses tumor growth and inhibits tumor metastasis in vivo . These polymers show promise in the treatment of cancer without the onset of resistance. Graphical abstract: A series of biodegradable block copolymers are synthesized and self-assembled into micelles of distinctive anticancer mechanism. These polymers are highly effective against various cancer cell types including multidrug-resistant ones, demonstrate an excellent in vivo antitumor effect while inhibiting tumor metastasis. More importantly, repeated use does not induce resistance. These macromolecules have excellent potential for use as anticancer agents.Image 1